The Thr92Ala polymorphism in the type 2 deiodinase gene is linked to depression in patients with COVID-19 after hospital discharge - Beltrão, Daniele Carvalhal de Almeida; Beltrão, Fabyan Esberard de Lima; Carvalhal, Giulia; Beltrão, Fabyanna Lethicia de Lima; Brito, Amanda da Silva; Silva, Hatilla dos Santos; Teixeira, Helena Mariana Pitangueira; Rodrigues, Juliana Lopes; de Figueiredo, Camila Alexandrina Viana; Costa, Ryan dos Santos; Pordeus, Liana Clebia De Morais; Vieira, Giciane Carvalho; et al. (Frontiers in Endocrinology, 2024)
Background: The Thr92Ala-DIO2 polymorphism has been associated with clinical outcomes in hospitalized COVID-19 patients and neuropsychiatric diseases. This study examines the impact of the Thr92Ala-DIO2 polymorphism on neuropsychological symptoms, particularly depressive symptoms, in patients who have had moderate to severe SARS-CoV-2 infection and were later discharged.Methods: Our prospective cohort study, conducted from June to August 2020, collected data from 273 patients hospitalized with COVID-19. This included thyroid function tests, inflammatory markers, hematologic indices, and genotyping of the Thr92Ala-DIO2 polymorphism. Post-discharge, we followed up with 68 patients over 30 to 45 days, dividing them into depressive (29 patients) and nondepressive (39 patients) groups based on their Beck Depression Inventory scores.We categorized 68 patients into three groups based on their genotypes: Thr/Thr (22 patients), Thr/Ala (41 patients), and Ala/Ala (5 patients). Depressive symptoms were less frequent in the Thr/Ala group (29.3%) compared to the Thr/Thr (59.1%) and Ala/Ala (60%) groups (p = 0.048). The Thr/Ala heterozygous genotype correlated with a lower risk of post-COVID-19 depression, as shown by univariate and multivariate logistic regression analyses. These analyses, adjusted for various factors, indicated a 70% to 81% reduction in risk.Our findings appear to be the first to show that heterozygosity for Thr92Ala-DIO2 in COVID-19 patients may protect against post-COVID-19 depression symptoms up to two months after the illness.